THE ROLE OF TRADITIONAL FARM RISK MANAGEMENT STRATEGIES ON REDUCING CREDIT RISK IN TANZANIA AGRICULTURAL LENDING - Ntulo, Edward; Hepelwa, Aloyce Shaban (Applied Studies in Agribusiness and Commerce, 2025)
Agricultural financing enhances food security, job creation, a transition from subsistence to commerce farming, and strengthens the overall economy. However, due to unfavorable weather and market conditions there is limited financing directed towards agriculture especially in developing countries. Despite smallholder farmers’ high adoption rate of traditional risk management strategies to minimize these risks, little has been done to examine its moderating role on the relationship between agricultural risks and credit risks. Thus, this study examines the role of farm business risk management strategies on minimizing the influences of production and market risk on smallholder farmers loan repayment capacity. The quantitative study used pooled cross-sectional data from a Tanzanian commercial bank from 2019 to 2021, covering 1,277 smallholder farmers from different administrative regions. Using binary interaction effect logistic regression analysis model, the study’s results indicate that irrigation, mechanization, and off-farm diversification significantly minimizes the effects of production and market risk amongst smallholder farmers in Tanzania, an indication that traditional risk management strategies are effective tools amongst smallholder farmers. On the contrary, on-farm diversification strengthens the influence of production and market risk on loan repayment amongst the smallholder farmers in Tanzania, the results that can be influenced by a number of factors, including poor diversification knowledge among smallholder farmers. In light of these findings, the study recommends that policy makers and other development partners to develop agricultural infrastructure and provide more extension agents that can educate smallholder farmers on the best practices on traditional risk management.